A novel test of flexible planning in relation to executive function and language in young children. Issue 4 (15th April 2020) - Miller, Rachael; Frohnwieser, Anna; Ding, Ning; Troisi, Camille A.; Schiestl, Martina; Gruber, Romana; Taylor, Alex H.; Jelbert, Sarah A.; Boeckle, Markus; Clayton, Nicola S.
Abstract : In adult humans, decisions involving the choice and use of tools for future events typically require episodic foresight. Previous studies suggest some non-human species are capable of future planning; however, these experiments often cannot fully exclude alternative learning explanations. Here, we used a novel tool-use paradigm aiming to address these critiques to test flexible planning in 3- to 5-year-old children, in relation to executive function and language abilities. In the flexible planning task, children were not verbally cued during testing, single trials avoided consistent exposure to stimulus–reward relationships, and training trials provided experience of a predictable return of reward. Furthermore, unlike most standard developmental studies, we incorporated short delays before and after tool choice. The critical test choice included two tools with equal prior reward experience—each only functional in one apparatus. We tested executive function and language abilities using several standardized tasks. Our results echoed standard developmental research: 4- and 5-year-olds outperformed 3-year-olds on the flexible planning task, and 5-year-old children outperformed younger children in most executive function and language tasks. Flexible planning performance did not correlate with executive function and language performance. This paradigm could be used to investigate flexible planning in a tool-use context in non-human species.